ANALISIS FASILITAS PENGELOLAAN LABORATORIUM DALAM MENDUKUNG KEGIATAN PRAKTIKUM BIOLOGI DI SMA N 1 DAN SMA KRISTEN DI DUMOGA TIMUR - Michelle Chantika Umboh; Aser Yalindua; Emma M Moko (SOSCIED, 2023)
There are problems with the layout of the biology internship room which does not meet laboratory standards. Tools and materials for practice are not complete. Laboratory management facilities have not supported student learning and the purpose of this study was to determine the biology laboratory management facilities of SMA N 1 Dumoga and SMA Kristen Dumoga Dumoga East to support academics. The method used is descriptive and qualitative. The results showed the overall level of readiness of the biology laboratory of SMA N 1 Dumoga and SMA Kristen Dumoga Dumoga Timur. A total of 78 schools met the readiness criteria, 58 schools met the readiness criteria to support student learning, data on the readiness of practicum tools and materials in each school reached 77.5% of schools met the readiness criteria, 57.5% of schools met the readiness criteria. sufficient readiness criteria, the results of the assessment through filling out the questionnaire distributed to students showed that the respondent scored 70% and respondent 2 scored 66%. Based on the results of research conducted in 2 schools SMA N 1 Dumo ga and SMA Kristen Dumoga Dumoga East regarding the management of laboratory facilities supporting biology learning, it can be concluded that the laboratory conditions Standardization of biology experiment laboratories are not good. this can be proven from the results of data analysis obtained. Keywords: Learning analysis, Laboratory, qualitative descriptive